A violência contra a mulher nas tramas dialógicas dos comentários on-line da Folha de S.Paulo - Tomás, Renata Nobre (2019)
This thesis focuses on the study of the perception of violence against women in Folha de S.Paulo‟s online comments. The concept of violence adopted in this work is based mainly on the postulates of Michaud (1989), Aranha (1997), Chaui (2017) and Bourdieu (2017), who consider as violence not only physical damages, but also psychological and symbolic ones. Violence here is analyzed in a relationships‟ weft: violence itself as an event, the account of this fact – constructed by the mediatic instance – and the readers‟ comment on these news/events. Our research problem seeks to answer the following question: how do the enunciators of Folha de S.Paulo’s online commentaries position themselves regarding news about violence against women? Our hypothesis is that violence is more easily identifiable by readers in acts than in states of violence and that, to position themselves in relation to the fact reported in the news, reveal in their comments gender stereotypes present in our society. Thus, this research has as general objective to analyze the dialogical relations present in the Folha de S.Paulo's online comments in order to investigate the readers‟ positions regarding the acts and states of violence practiced against women. Our specific objectives are: to describe the treatment given by digital journalism to online comment; present the configuration and the functioning of the online comment genre in Folha de S.Paulo newspaper; identify, describe and analyze the linguistic-discursive strategies of the online commentaries that show the positions of the enunciators with regard to violence against women. This thesis is based on the theoretical perspective of Dialogical Analysis of Discourse (ADD). Among the scholars of this aspect, we prioritize Bakhtin (2003a, 2015a, 2016a) and Volóchinov (2017). The concepts developed throughout the Bakhtin thought, dialogism, enunciation and discourse genre were indispensable to this work. We also resort to Brazilian researchers who have been dedicated to studying the conception of language theorized by these Russian thinkers. Among them, we highlight Brait (2008a, 2016b), Fiorin (2008) and Faraco (2009). We are also based on authors who establish categories of analysis for language studies, such as Authier-Revuz (2004) and Maingueneau (1997, 2008, 2013). To compose our corpus, we selected 48 news and its 675 comments published in the period from January 1 to June 30, 2017 in Folha de S.Paulo‟s newspaper. We find that the online comment genre is recurrent in digital journalism and goes through frequent changes in its structural plan and publicating standards. Concerning the perception of violence against women, we find that even in the acts, there is the euphemization of the damages caused, the naturalization of the violence, the distrust of the victim's report and her blame for the violence suffered. As for the states, some readers recognize the violence, as occurred with the presidential speech and the photograph posted by medical students on social networks. In the news dealing with harassment and inequality in power relations, however, the commentary oscillates between blaming the victim and not identifying the violence